Leaf litter of Erythrina crista-galli L. (ceibo): trophic and substratum resources for benthic invertebrates in a secondary channel of the Middle Paraná River. - Ramseyer, Ursula (2009)
The decomposition of Erythrina crista-galli L. (Leguminosa) leaf litter and its colonization by invertebrates were studied in a secondary channel of the Middle Paran´a River. This species is native to and very abundant in South America in riverside areas and in Argentina it is known as ‘ceibo’. The objectives were to estimate the E. crista-galli leaves’ decomposition rate,  to determine the proportion of functional feeding groups of invertebrates throughout the process of decomposition, and to evaluate the use of leaf detritus by the benthic invertebrates. The leaves were collected at abscission and 6 g dry weight were placed in 5 mm mesh nylon bags. The samplings were carried out between May and September 2002 and six replicates were collected after 7, 14, 28, 56 and 112 days. The decomposition rate (k) calculated over 112 days of decomposition was 0.0129 d−1. Invertebrate densities increased with the progressive decomposition of the leaves, reaching the maximum at 14 days (306 ind g−1 dw leaf−1) and 112 days (298 ind g−1 dw leaf−1). The highest species richness (18.5) was found at 7 days of leaf decomposition. Colonization of decomposing leaves was dominated by Diptera Chironomidae (Polypedilum spp., Phanopsectra sp.), Crustacea (Cladocera, Ostracoda), Oligochaeta Naididae (Pristina americana, Slavina evelinae, and S. isochaeta), and Mollusca (Limnoperna fortunei). The shredders were dominant at the begining of the decomposition process and the collector-filterers increasing at the end of the period because of the highest density of Limnoperna fortunei which used the leaf litter as substratum.Limnoperna fortunei which used the leaf litter as substratum.